Whole transcriptome analysis of the Atlantic cod vaccine response reveals subtle changes in adaptive immunity - Solbakken, Monica Hongrø; Jentoft, Sissel; Reitan, Trond; Mikkelsen, Helene; Jakobsen, Kjetill Sigurd; Seppola, Marit (Comparative Biochemistry and Physiology Part D: Genomics and Proteomics, 2019)
Atlantic cod has lost the Major Histocompatibility complex class II pathway – central to pathogen presentation, humoral response and immunity. Here, we investigate the immunological response of Atlantic cod subsequent to dip vaccination with Vibrio anguillarum bacterin using transcriptome sequencing. The experiment was conducted on siblings from an Atlantic cod family found to be highly susceptible towards vibriosis where vaccination has demonstrated improved pathogen resistance. Gene expression analyses at 2, 4, 21 and 42 days post vaccination revealed GO-term enrichment for muscle, neuron and metabolism-related pathways. In-depth characterization of immune-related GO terms demonstrated down-regulation of MHCI antigen presentation, C-type lectin receptor signaling and granulocyte activation over time. Phagocytosis, interferon-gamma signaling and negative regulation of innate immunity were increasingly up-regulated over time. Individual differentially expressed immune genes implies weak initiation of acute phase proteins with little or no inflammation. Furthermore, gene expression indicates presence of T-cells, NK-like cells, B-cells and monocytes/macrophages. Three MHCI transcripts were up-regulated with B2M and SEC61 . Overall, we find no clear immune-related transcriptomic response which could be attributed to Atlantic cod's alternative immune system. However, we cannot rule out that this response is related to vaccination protocol/sampling strategy. Earlier functional studies demonstrate significant memory in Atlantic cod post dip vaccination and combined with our results indicate the presence of other adaptive immunity mechanisms. In particular, we suggest that further investigations should look into CD8+ memory T-cells, γδ T-cells, T-cell independent memory or memory induced through NK-like/other lymphoid cells locally in the mucosal lining for this particular vaccination strategy.